Characterization of coaggregation between Bacteroides gingivalis T22 and Fusobacterium nucleatum T18. - Kinder, S A (1989)
Bacterial adherence is a key factor in the colonization of the oral ecosystem, yet little is known about the mechanisms by which the pathogen Bacteroides gingivalis adheres in the periodontal environment. We examined the ability of strains of B. gingivalis to coaggregate with selected microorganisms isolated from the subgingival microbiota of the cynomolgus monkey. A strong interaction was demonstrated between strains of B. gingivalis and Fusobacterium nucleatum, whereas less pronounced or no interaction was observed with other oral isolates. Electron microscopic examination of coaggregates revealed large masses of bacteria, in which the fusiform F. nucleatum T18 and coccobacillary B. gingivalis T22 cells formed a woven pattern. To investigate this interaction and the nature of the bacterial cell surface molecules involved, we used a microcoaggregation assay. Galactose and galactose-related sugars blocked coaggregation, in contrast with the lack of effect of glucose or glucose-related sugars. The ability of F. nucleatum T18 cells to coaggregate was diminished by pretreatment with pronase. Pretreatment of B. gingivalis T22 cells with pronase resulted in an inhibition of coaggregation, whereas pretreatment with sodium metaperiodate completely abolished coaggregation. These data suggest that the coaggregation between B. gingivalis T22 and F. nucleatum T18 represents a carbohydrate-lectin interaction, mediated by a galactose-containing carbohydrate on B. gingivalis T22 and a protein on F. nucleatum T18.